An evaluation of respiratory administration of measles vaccine for prevention of acute lower respiratory infections in children - Jadhav Suresh S; Zgaga Lina; Huda Tanvir; Nair Harish; Theodoratou Evropi; Higginson Daisy; Omer Saad B; Rudan Igor; Campbell Harry (BMC, 2011)
Abstract Background Measles was responsible for an estimated 100,000 deaths worldwide in 2008. Despite being a vaccine-preventable disease, measles remains a major cause of morbidity and mortality in young children. Although a safe and effective injectable measles vaccine has been available for over 50 years it has not been possible to achieve the uniformly high levels of coverage (required to achieve measles eradication) in most parts of the developing world. Aerosolised measles vaccines are now under development with the hope of challenging the delivery factors currently limiting the coverage of the existing vaccine. Methods We used a modified CHNRI methodology for setting priorities in health research investments to assess the strengths and weaknesses of this emerging intervention to decrease the burden of childhood pneumonia. This was done in two stages. In Stage I, we systematically reviewed the literature related to emerging aerosol vaccines against measles relevant to several criteria of interest. Although there are a number of different aerosol vaccine approaches under development, for the purpose of this exercise, all were considered as one intervention. The criteria of interest were: answerability; cost of development, production and implementation; efficacy and effectiveness; deliverability, affordability and sustainability; maximum potential impact on disease burden reduction; acceptability to the end users and health workers; and effect on equity. In Stage II, we conducted an expert opinion exercise by inviting 20 experts (leading basic scientists, international public health researchers, international policy makers and representatives of pharmaceutical companies). The policy makers and industry representatives accepted our invitation on the condition of anonymity, due to the sensitive nature of their involvement in such exercises. They answered questions from the CHNRI framework and their "collective optimism" towards each criterion was documented on a scale from 0 to 100%. Results The panel of experts expressed mixed feelings about an aerosol measles vaccine. The group expressed low levels of optimism regarding the criteria of likelihood of efficacy and low cost of development (scores around 50%); moderate levels of optimism regarding answerability, low cost of production, low cost of implementation and affordability (score around 60%); and high levels of optimism regarding deliverability, impact on equity and acceptability to health workers and end-users (scores over 80%). Finally, the experts felt that this intervention will have a modest but nevertheless important impact on reduction of burden of disease due to childhood pneumonia (median: 5%, interquartile range 1-15%, minimum 0%, maximum 45%). Conclusion Aerosol measles vaccine is at an advanced stage of development, with evidence of good immunogenicity. This new intervention will be presented as a feasible candidate strategy in the campaign for global elimination of measles. It also presents an unique opportunity to decrease the overall burden of disease due to severe pneumonia in young children.